Different surfactants improve calcium uptake into leaf and fruit of ‘Washington navel’ sweet orange and reduce albedo breakdown - Pham, T.; Singh, Zora; Behboudian, M. (Marcel Dekker, Inc., 2012)
Albedo breakdown (AB) in sweet orange fruit is a physiological disorder, characterized by cracks in albedo resulting in puffiness of peel and causes serious economic losses. Lower levels of calcium (Ca) in fruit have been associated with AB. The efficacy of different surfactants in improving Ca uptake into leaf and fruit, consequently reducing AB and improving fruit quality of ‘Washington Navel’ sweet orange was tested. Surfactants enhanced the uptake of Ca in leaf, rind, and pulp of the fruit and reduced AB compared to the calcium-only treatment and ‘Tween 20’ was the most effective. In conclusion, five foliar sprays of aqueous solution containing 2% calcium nitrate [Ca(NO3)2] and 0.05% ‘Tween 20’ starting from 81 days after full bloom (DAFB) at 10-day intervals improved Ca uptake in leaf, rind and pulp of fruit and reduced the incidence of AB in ‘Washington Navel’ and maintained the other important fruit quality parameters.